PENGARUH MOTIVASI DAN SIKAP TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENGAMBIL PROFESI CHARTERED ACCOUNTANT (CA) PADA UNIVERSITAS ISLAM SWASTA DI KOTA MEDAN - Nisa, Sayyidatun (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
This study aims to examine and analyze the influence of the level of understanding of Chartered Accountant (CA), motivation to obtain a Chartered Accountant (CA) and attitudes regarding Chartered Accountant (CA) on the interest of students to take up the profession Chartered Accountant (CA) at Private Islamic Universities in Medan City. This research uses the associative quantitative research. This study uses primary data where data is collected using a questionnaire. This research was conducted on the seventh semester students of class 2015 at the Private Islamic University in Medan City with a population of 747 students and a sample of 261 respondents. Data analysis techniques in this study used descriptive statistics, classic assumption tests, multiple linear regression analysis, hypothesis testing and coeficient of determination tests. The results of the analysis show that the level of understanding of Chartered Accountant (CA) affects the interest of students to take the chartered accountant profession. Motivation to get a Chartered Accountant (CA) affects the interest of students to take the chartered accountant profession. The attitude about Chartered Accountant (CA) affects the interest of students to take the chartered accountant profession. The results of the analysis prove that simultaneously the Level of Understanding of Chartered Accountant (CA), motivation to get a Chartered Accountant (CA) and attitudes regarding Chartered Accountant (CA) influence the interest of students to take the chartered accountant profession.